Transport Processes in Porous Media by Self-Potential Method - Valeria Giampaolo; Daniela Calabrese; Enzo Rizzo (Applied and Environmental Soil Science)
A controlled diffusion/infiltration column experimental activity was carried out with the aim of monitoring the leakage of a salty water plume by time-lapse self-potential (SP) measurements. In particular, three tracer tests with different NaCl concentrations (6.00, 1.00, and 0.25 g L−1) were performed and all the measured SP signals showed a sharp reduction corresponding to the arrival of saline front with negative electrical potential values (−78.99±3.24 mV, −54.52±2.28 mV, and −24.12±1.21 mV) which decrease with increasing volume of tracer introduced into the column. Then, measured self-potential values were converted into salt concentration ones by the Planck-Henderson equation and sand diffusion (D) and longitudinal dispersivity (αL) values were estimated by modelling the transport equations in the COMSOL Multiphysics environment. Finally, the results show that measured and estimated NaCl concentrations are well correlated.